Historiografski tekst i historijski kontekst historiografija o Nijemcima na prostoru Jugoslavije 1919. - 2019. - Janjetović, Zoran D. (2019)
Rad zavisno od vremena i mjesta nastanka analizira historiografsku literaturu koja je nastala o Nijemcima (folksdojčerima) na teritoriju koji je obuhvaćala Jugoslavija posljednjih sto godina.
The paper deals with the representation of the Ethnic Germans (Volksdeutsche) in the historiography of the territory once comprising Yugoslavia. The author divides his subject matter according to regions (Slovenia, Croatia, Serbia, and Bosnia-Herzegovina) and periods (inter-war, communist, and post-communist). During the first period, the Volksdeutsche were not a prominent topic in historiography of the three leading Yugoslav peoples, not even in Slovenia, which had the longest history of ethnic strife between the Slovenes and the Germans. It was the Ethnic German authors who published the most works on the Volksdeutsche in this period. Most of them appeared in the 1930s, as many Danube Swabian settlements celebrated the 150th or 200th anniversaries of the arrival of the Germans. After WWII, in which the Ethnic Germans had sided with the invaders and were afterwards collectively punished by the new communist authorities, they acquired the image of the “bad guys” of post-war historiography. During the first 15-odd years, works on them were scarce, although several official papers and memoranda enumerating their war crimes and treasonable activities before and during WWII were written soon after the end of the war. In the course of the 1960s, several important works appeared and set the trend for the 1970s and part of the 1980s. Most of them were published in Slovenia. These works also covered the longest time span. In other parts of Yugoslavia, works on the Volksdeutsche usually dealt with their colonization or with WWII. Works on WWII always insisted on German war crimes, persecution of Jews, and combat against the Partisans. Since the mid-1980s, the image of the Volksdeutsche has become more realistic and less biased.
Bibliografske bilješke uz tekst ; bibliografija: str. 38-55.
Sažetak ; Summary.
Keywords: Nijemci -- Folksdojčeri -- Historiografija -- Drugi svjetski rat -- Logori; Jugoslavija